Do Gender and Age Matter in Employment – Sectoral Growth Relationship Over the Recession and Expansion - Butkus, Mindaugas; Dargenytė-Kacilevičienė, Laura; Matuzevičiūtė, Kristina; Ruplienė, Dovilė; Šeputienė, Janina (Ekonomika, 2022)
This paper examines age- and gender-specific employment sensitivity to growth across different economic sectors. By applying a non-linear panel specification of Okun’s first-difference equation on EU-28 countries for 1995-2019, we estimate age-, gender-, and sector-specific employment intensities to growth. Our study examines the ability of growth in different sectors to generate total employment opportunities. Results show that regardless of gender or age, the employment growth is mainly driven by the services sector growth. Still, if we consider the share of a sector in the economy, the construction sector is found to be the most employment-intensive. Our estimates show that the male and female employment intensities of growth in services are quite equal. Considering the employment opportunities by gender, the main differences were found in the construction sector. Expansion and recession were confirmed to have a significantly different effect on the employment rate only in the construction sector regardless of age and gender.
Keywords: economic sectors; economic growth; youth unemployment; gender; employment intensity